A sustainable approach to enhance fruit shelf‐life: Edible coating from pineapple fruit waste biomass. Issue 15 (19th December 2020) - Bhattacharjee, Satyajit; Haldar, Dibyajyoti; Manna, Mriganka Sekhar; Gayen, Kalyan; Bhowmick, Tridib Kumar
Abstract: The quality and commercial value of fruits largely depend on color, texture, appearance, nutritional value, and other factors that cease the growth of the microbes causing food spoilage. Coating with suitable edible material would keep fruits fresh for a considerable time after their harvest till it reaches to the demanding consumers. The nonedible portions (peel, crown) of pineapple are identified as an inexpensive source for the production of such edible coating material. The present work is focused on the extraction and physicochemical analysis of cellulose prepared from waste bio‐mass of pineapple fruit. Physicochemical characterization of the cellulose is performed using X‐ray diffraction, Fourier‐transform infrared spectroscopy and scanning electron microscopy. The extracted cellulose is converted to carboxymethyl cellulose and formulated as a coating film in conjugation with other suitable substances. The formulated coating is applied on banana fruit to check the performance of protection against the natural degradation of the fruit. FTIR analysis of the extracted cellulose has confirmed the removal of lignin and hemicelluloses molecules from the waste biomass of pineapple. X‐ray diffraction analysis has shown the crystal size of extracted cellulose was 3.23 nm with 35.62% crystallinity. Degree of substitution (DS) is estimated 0.523 for carboxymethyl cellulose prepared from the extracted cellulose. Application of coating has shown the increment in shelf‐life period of banana in comparison with control up to 8 days of storage at ambient condition. This study has demonstrated a sustainable process to transform waste biomass into carboxymethyl cellulose based coating for improving storage capacity of banana fruit. Abstract :